(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Chronic diseases pose a significant public health challenge globally, contributing to a substantial burden of morbidity, mortality, and healthcare costs. Public health nurses play a crucial role in preventing and managing chronic diseases through a variety of strategies aimed at promoting health, preventing disease progression, and improving quality of life. This article provides a comprehensive overview of chronic disease management strategies employed by public health nurses, including preventive interventions, patient education, care coordination, and community-based initiatives. Key principles, evidence-based practices, challenges, and future directions in chronic disease management within the context of public health nursing are discussed.